If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -9 = 11 Reorder the terms: -9 + 4a = 11 Solving -9 + 4a = 11 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 4a = 11 + 9 Combine like terms: -9 + 9 = 0 0 + 4a = 11 + 9 4a = 11 + 9 Combine like terms: 11 + 9 = 20 4a = 20 Divide each side by '4'. a = 5 Simplifying a = 5
| 3y^2+8y-60=0 | | 13a-2b+5c+8a-7b= | | -9x^2*2x= | | x=288 | | 10x+2=3x+65 | | 4x^2*3x^2= | | 9x^2+13x-120=0 | | 6x-2(5x+2)=-4 | | -2+y=4 | | x^2-3x-34=-7x-2 | | x^2-5x+16=10 | | 9x+20=-20 | | x^2+160x+1000= | | x+(0.22x)=500 | | -18+6x=-8x+10 | | 12s-4=8s | | 6y=y+25 | | 9a+40=4 | | 2a-9=1 | | x^2(2x-3)+6x(2x-3)+9(2x-3)=0 | | 5x-9=12x-8 | | x^2-11x-27=-6x-3 | | 0=4x+3 | | 5x-9=12-8 | | 3(n-6)=2(5-2n) | | 7a+24=3 | | 6x-11=4x+7 | | (2x^3-x^2+7)(2x+3)= | | -3x+0=-6 | | 3(m+7)=5(3-m) | | 82.5+94.7+87.9+x= | | 7a+8=29 |